THE EFFECT OF VISUAL COMMUNICATION ON “CANTIK FEST” IN TOKOPEDIA TOWARDS BUYING INTEREST OF FEMALE CONSUMER IN JAKARTA - Marilyn; Sitinjak, Tony (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2022)
Humans are facilitated by technological advances where consumers can do online shopping anywhere and anytime through the E-Commerce platform. Tokopedia has one of the biggest campaigns, namely “Cantik Fest” and creates a visual communication, one of that is through banners in Tokopedia application which is related to how prospective buyers will be interested in shopping online. The purpose of this research is to find out and get an idea about the effect of visual communication